Enemy Number One : the United States of America in Soviet ideology and propaganda 1945-1959 - Magnúsdóttir, Rósa 1974- (Oxford scholarship online, 2019)
'Enemy Number One' tells the story of Soviet propaganda and ideology toward the United States during the early Cold War. From Stalin's anti-American campaign to Khrushchev's peaceful coexistence, this work covers Soviet efforts to control available information about the United States and to influence the development of Soviet-American cultural relations until official cultural exchanges were realized between the two countries